Sosialisasi Cyberbullying Dan Cybersecurity Pada Siswa SDN 3 Kalijaga Timur - Lalu Kerta Wijaya; M Rahmatul Aqib; Bruin Tino; Ahmad Sazali; Siti Radina Erza; L.Hidayatullah (Jurnal Teknologi Informasi untuk Masyarakat, 2026)
The rapid development of digital technology has significantly influenced children’s lives, including elementary school students. However, the use of digital technology without adequate digital literacy understanding may lead to various problems, such as cyberbullying and cybersecurity threats. Low awareness of safe and responsible digital behavior makes students vulnerable to online harassment and cybercrime. This community service activity aimed to improve elementary school students’ understanding of cyberbullying and cybersecurity through an educational socialization program. The activity was conducted on December 16, 2025, at SDN 3 Kalijaga Timur, involving 52 fifth- and sixth-grade students. A qualitative approach was applied through interactive lectures, the use of visual media in the form of educational posters, and evaluation through quizzes. The results showed that students demonstrated high enthusiasm during the activity and were able to understand the delivered materials well. All students successfully answered the quiz questions correctly, indicating an improvement in their understanding of the dangers of cyberbullying and the importance of maintaining personal security in the digital environment. Therefore, this socialization activity is expected to help develop safe, ethi cal, and responsible digital behavior among students from an early age.